Food Alone May Not Provide Sufficient Micronutrients for Preventing Deficiency - Misner Bill (Taylor & Francis Group, 2006)
Abstract The American Dietetic Association (ADA) has stated that the best nutritional strategy for promoting optimal health and reducing the risk of chronic disease is to wisely choose a wide variety of foods. Seventy diets were computer analyzed from the menu of athletes or sedentary subjects seeking to improve the quality of micronutrient intake from food choices. All of these dietary analyses fell short of the recommended 100% RDA micronutrient level from food alone. Therefore, based on diets analyzed for adequacy or inadequacy of macronutrients and micronutrients, a challenging question is proposed: "Does food selection alone provide 100% of the former RDA or newer RDI micronutrient recommended daily requirement?"